On the Issue of Sense Benchmarks of Behavior (Economic-Legal Aspects) - Дудченко, Валентина Віталіївна; Дудченко, В. В.; Дудченко, Валентина Витальевна; Dudchenko, Valentyna V.; Dudchenko, Valentina V.; Цуркан-Сайфуліна, Юлія Василівна; Цуркан-Сайфуліна, Ю. В.; Цуркан-Сайфулина, Юлия Васильевна; Tsurkan-Saifulina, Yuliia V.; Цуркан, Олександр Васильович; Цуркан, О. В.; Цуркан, Александр Васильевич; et al. (ASERS Publishing, 2018)
This paper attempts to analyze the leakages, essence, the peculiarity of normative meanings and their connection with public values. From the ability to cognize "that to which to aspire to", a person becomes capable to understand a meaning of deeds. To solve a practical question in the legal sphere, that means to say what is proper. The authors have proved the difference between analytical judgments a posteriori and, thus, justified the method's reform and the need for a holistic consideration ofall things, including legal, in epistemology. It is revealed that the method of describing the meaning is hermeneutics and that the peculiarity of the teleological (target) interpretation is the orientation towards the goal, on the principles. The opportunity to motivate actions through normative meanings is substantiated.

У цій роботі зроблено спробу проаналізувати витоки, сутність, особливість нормативних значень та їх зв’язок із суспільними цінностями. Від здатності пізнавати «те, до чого прагнути», людина стає здатною розуміти сенс вчинків. Вирішити практичне питання в юридичній сфері, це означає сказати, що є належним. Автори довели різницю між аналітичними судженнями a posteriori і, таким чином, обґрунтували реформування методу та необхідність цілісного розгляду всього, в тому числі і правового, в епістемології. Виявлено, що методом опису значення є герменевтика, а особливістю телеологічної (цільової) інтерпретації є орієнтація на мету, на принципи. Обґрунтовано можливість мотивувати дії через нормативні значення.
Dudchenko V. V. On the Issue of Sense Benchmarks of Behavior (Economic-Legal Aspects) / V. V. Dudchenko, Yu. V. Tsurkan-Saifulina, O. V. Tsurkan // Journal of Advanced Research in Law and Economics. - V. 9. - N. 8(38). - ASERS Publishing, 2018. - P. 2562-2569.
Keywords: normative meanings; analytical judgment; method reform; hermeneutics; directly active law; нормативні значення; аналітичне судження; реформа методу; герменевтика; право прямої дії; Research Subject Categories::LAW/JURISPRUDENCE